Reading Subaltern studies : critical history, contested meaning, and the globalisation of South Asia - Ludden, David E. (Delhi : Permanent Black, 2002)
Contributed articles.
Brief history of subalternity / David Ludden -- Peasantry, politics, and historiography : critique of new trend in relation to Marxism / Javeed Alam -- Subaltern studies II : a review article / Sangeeta Singh ... [et al.] -- Significance of non-subaltern mediation / Ranajit Das Gupta -- Subaltern autonomy and the national movement / B.B. Chaudhuri -- Recovering the subject : Subaltern studies and histories of resistance in colonial South Asia / Rosalind O'Hanlon -- Dis/appearance of subalterns : a reading of a decade of Subaltern studies / Jim Masselos -- Situating the subaltern : history and anthropology in the Subaltern studies project / K. Sivaramakrishnan -- Conflict and connection : rethinking colonial African history / Frederick Cooper -- Subaltern studies : radical history in the metaphoric mode / Henry Schwarz -- Drought and TADA in Adilabad / K. Balagopal -- Relevance (or irrelevance) of Subaltern studies / Vinay Bahl -- Decline of the subaltern in Subaltern studies / Sumit Sarkar.
Includes bibliographical references.
"Additional bibliography": (p. [436]-442).
Keywords: South Asia -- Historiography; South Asia -- History; India -- History